Ethnobotany, phytochemistry, and biological properties of three naturally associated Mediterranean species - Khadija Benamar, Saad Ibnsouda Koraichi, Kawtar Fikri-Benbrahim (Journal of Applied Pharmaceutical Science, 2025)
Chamaerops humilis (C. humilis), Olea europea var Sylvestris (O. oleaster), and Asparagus albus (A. albus) are three plant species native to the Mediterranean basin. They are often associated in nature. In different countries of the Mediterranean area, they are used in folk medicine in order to treat several ailments, such as urinary, digestive, respiratory, neurologic, and metabolic diseases. The numerous traditional therapeutical uses of these three plant species have led to the completion of several studies demonstrating scientifically their biological activities. However, as regards A. albus, only a few studies were carried out in this context. This review has the objective of documenting and analyzing different works concerning the ethnomedicinal uses, chemical composition, and bioactive potential of these three medicinal plants, in order to provide researchers with a global database of biological properties that have been demonstrated and to identify gaps for further studies. The electronic databases used for data collection are Google Scholar, Pub Med, Pub Chem, Science Direct, and Scopus. The results of this study show that thanks to their richness in bioactive compounds, C. humilis, O. oleaster, and A. albus exhibit several biological activities that can be exploited in the medical and agro-food fields.
Keywords: Chamaerops humilis, Olea oleaster, Asparagus albus, ethnobotany, phytochemistry, pharmacology